2008
DOI: 10.1002/mds.22009
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related changes in increase of dopaminergic neurons in the olfactory bulb of Parkinson's disease patients

Abstract: Gender differences in dopaminergic related neurodegenerative diseases have hardly been studied until now. It is generally accepted that more men than women suffer from Parkinson's disease. One of the most prevalent symptoms in Parkinson's patients, hyposmia, does not show gender differences, while normally the sense of smell is better developed in females. Whether the change in dopamine in the olfactory bulb contributes equally to hyposmia in male and female Parkinson's patients is the subject of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 42 publications
4
55
1
1
Order By: Relevance
“…Our results suggest that olfactory dysfunction in PD is associated with atrophy in olfactory-eloquent regions of the limbic and paralimbic cortex and might therefore not be restricted to deficient sensory transmission in the olfactory bulb (Huisman et al, 2008). Further analysis showed that olfactory-related atrophy is not a consequence of generalized brain atrophy but seems to be rather a regional effect; total intracranial and gray matter volumes did not differ between all groups.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our results suggest that olfactory dysfunction in PD is associated with atrophy in olfactory-eloquent regions of the limbic and paralimbic cortex and might therefore not be restricted to deficient sensory transmission in the olfactory bulb (Huisman et al, 2008). Further analysis showed that olfactory-related atrophy is not a consequence of generalized brain atrophy but seems to be rather a regional effect; total intracranial and gray matter volumes did not differ between all groups.…”
Section: Discussionmentioning
confidence: 51%
“…A prevalent symptom at early stages of PD is olfactory impairment (Ansari and Johnson, 1975). Results from postmortem studies revealed pathological changes (Lewy body formation) in the olfactory bulb (Huisman et al, 2008) but also in other brain regions related to olfaction, such as the anterior olfactory nucleus (Pearce et al, 1995), the piriform cortex (Braak et al, 2003;Silveira-Moriyama et al, 2009), the amygdaloid complex (Harding et al, 2002;Braak et al, 2003), the entorhinal cortex, and the hippocampal formation (Braak et al, 2003). Using functional magnetic resonance imaging in PD patients, our previous findings indicated altered neuronal activity in the amygdaloid complex and hippocampal formation during olfactory stimulation (Westermann et al, 2008;Welge-Lüssen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These neurons are calciumdependent autonomous pacemakers (91). However, there are no signs of cell loss in the olfactory bulb in spite of deficits in olfaction being a harbinger of the motor symptoms in PD (50,94). This does not mean that a reliance upon calcium is a bad thing though, as this region is capable of adult neurogenesis (90).…”
Section: Pd Is Not Just a Disease Of Dopaminergic Neurons In The Sncmentioning
confidence: 99%
“…12 The existence and targeting of neuronal loss in the olfactory system is controversial. 48,49 This issue is complicated by the neurogenesis in this region. 50 There are several other regions that have been reported to have either neuronal loss or Lewy pathology in PD, many in single studies.…”
Section: Introductionmentioning
confidence: 99%